Crisis de hegemonía política en América Latina - Quijano, Aníbal (1973)
This article was scanned by the Aurelio Espinosa Polit Ecuadorian Library.In this opportunity we will try to present a scheme of analysis on the problem of the Latin American political crisis, considered in a double perspective. On the one hand, as a problem of crisis of political hegemony and, on the other hand, therefore, as a problem of crisis of the State in Latin America. And it is on the basis of such a scheme that we will finally try to explore in a very brief way the alternatives that seem to appear in the Latin American perspective to get out, perhaps not to solve, but at least to get out, of the crisis of political hegemony.